CHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITIES OF THE ESSENTIAL OILS AND THE METHANOLIC EXTRACTS OF BUNIUM INCRASSATUM AND BUNIUM ALPINUM FROM ALGERIA - Hayet, El Kolli; Hocine, Laouer; Meriem, El Kolli (Journal of the Chilean Chemical Society, 2017)
In order to study the curing proprieties of endemic Algerian plants, it is evaluated the chemical composition and four biological activities of two Apiaceae species, which are Bunium incrassatum and Bunium alpinum. The essential oils (EO) obtained by hydro-distillation of dried aerial parts were analyzed by GC/ MS. The antibacterial activity was investigated using the disc diffusion assay against ten (10) Gram-positive and Gram-negative bacteria. Antioxidant activity was evaluated by DPPH technique. Methanolic extracts (Me EXTs) were used in studying in vitro anti-inflammatory activity using egg albumin technique and in vitro anti-hemolytic activity using HBRC technique. The EO yield based on dried plant material was 0.09 % for B. incrassatum and 0.10 % for B. alpinum. Thirty-one compounds (corresponding to 97.19%) were identified for B. incrassatum. The main component was palmitic acid (18.39%). While twenty-four compounds (coresponding 87.33%) were identified for B. alpinum. The main component was caryophyllene oxide (33.84%). The study of antibacterial activity demonstrated that the EOs showed a modest antibacterial activity compared to gentamicin. The antioxidant activity revealed that EOs and Me EXTs demonstrated a very important anti-radical activity compared to standards (BHT, BHA, tocopherol, quercitin and rutin). The Me EXTs demonstrated also, significant antihemolytic and anti-inflammatory activities to those of standard (sodium diclofenac). It was found that all these activities are much related to the chemical composition of EO and Met EXTs. These activities could be exploited in the food industry for food preservation or in pharmaceutical industry.